Creation of heterojunction in CdS supported on N, S-rGO for efficient charge separation for photo-reduction of water to hydrogen - Alam Z.; Verma B.; Sinha A.S.K. (My University, 2025)
An efficient CdS supported on nitrogen and sulfur-doped reduced graphene oxide (N,S-rGO) has been prepared by a high-temperature gas-solid reaction for the first time. This catalyst was about ten times more efficient compared to pristine CdS in the dissociation of water to hydrogen. The high-temperature gas-solid reaction promotes chemical interaction between CdS and reduced graphene oxide (rGO) forming a heterojunction at the interface for transfer of photogenerated electrons from CdS to rGO. Doping of rGO with N and S enhances electron mobility and charge carrier density on the surface of the catalyst. The synergy between the efficient electron transfer, the enhanced electron mobility and the high charge carrier density results in a high activity of the prepared catalyst for photo-reduction of water to hydrogen. A detailed microstructural analysis for understanding the interaction amongst preparation technique, microstructure and activity, is also presented. © 2019 Hydrogen Energy Publications LLC